MOTIVATION OF PREGNANT WOMEN ABOUT BREAST CARE AT PUBLIC HEALTH CENTER PUTRI AYU - Arifarahmi Arifarahmi (Jurnal Akademika Baiturrahim Jambi, 2018)
Preparation that needs to be done during pregnancy is to do breast care. Breast care aimed to keep breast hygiene, flex and strengthen the nipple, prepare a flat nipple, and prepare ASI production. This is a descriptive research, it aimed to determine the description motivation of pregnant women about breast care at the public health center Putri Ayu Jambi city year 2017. It was conducted on August year 2017. Populations were pregnant women who who visited to check up of pregnancy at the public health center Putri Ayu jambi city on August as many as 38 people. The data collecting used by using questionnaire. Data analyzed as univariate.The result showed that respondents had low motivation were 18 respondents (47%) and respondents who had high motivation were 20 respondents (53%). Respondents who did not breast care were 16 respondents (42.1%) and respondents who breast care were 22 (54%).For the health personnel expected to improve of counseling to pregnant women during antenatal care service or pregnant women class.